Effect of methionine supplementation on methionine metabolism in growing cattle - B.D. Lambert; C.A. Löest; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2002)
Methionine is often the first limiting amino acid for growing cattle. This study was conducted to determine how methionine metabolism is regulated in the liver of growing steers. Six ruminally cannulated steers were used in a replicated 3 x 3 Latin square experiment. Either 0, 5, or 10 g/day L-methionine was infused into the abomasum. These treatments were designed to be deficient, adequate, and in excess of the steers' requirements for methionine. Methionine supplementation linearly increased protein deposition and decreased the activity of methionine synthase (a methionine conserving enzyme). However, it had little effect on activity of cystathionine synthase (an enzyme that produces cysteine from methionine). Our results suggest that methionine metabolism and regulation in cattle may vary from that in monogastrics.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Methionine; Amino acids; Growth